Modelação da ocorrência potencial de espécies com interesse para a conservação nos sítios classificados Peniche/Santa Cruz e Sintra/Cascais - Godinho, Lia Pinheiro (2015)
A modelação de ocorrência potencial tem sido muito utilizada para espécies com interesse para a conservação. Sabendo as condições ambientais preferenciais de cada espécie pode-se selecionar locais que possuam condições favoráveis para a reintrodução de espécies que, por diversas razões, não colonizaram aqueles locais e melhorar as acções de conservação relativamente aos núcleos populacionais efectivos. O objectivo deste trabalho baseou-se na definição das condições ambientais mais favoráveis para as espécies cominteresse para a conservação listadas nos anexos da Diretiva Habitats Armeria pseudarmeria, Dianthus cintranus subsp. cintranus, Verbascum litigiosum, Thymus villosus subsp. villosus, Ulex densus, Ruscus aculeatus, Omphalodes kuzinskyanae e Limonium multiflorum para posterior reintrodução dessas mesmas espécies em locais onde não estão presentes, mas onde já estiveram e que têm, por conseguinte, condições favoráveis para estas colonizarem. Pretende-se, igualmente, a definição das condições ambientais preferênciais para os táxones, que embora não constem nos anexos da Directiva Habitats, estão associadas às espécies com interesse conservacionista, entre elas está a Armeria welwitschii subsp. welwitschii, Ulex jussiaei subsp. congestus, Daucus halophilus, Limonium virgatum e Ilex aquifolium. Obteve-se como resultado final o perfil ecológico de cada espécie, melhorando assim o conhecimento relativamente às espécies alvo para uma melhor estratégia de conservação, uma base teórica que servirá como ferramenta para reintrodução futura destas espécies e ainda todo o conhecimento para o mapeamento da ocorrência potencial destas espécies nos sítios Peniche/Santa Cruz e Sintra/Cascais classificados na Rede Natura 2000. Palavras-chave: Perfil ecológico, Peniche/Santa Cruz, Sintra/Cascais, Modelação, Espécies protegidas, Rede Natura 2000; ABSTRACT: The modelling of potential occurrence has been widely used for species of interest to conservation. Knowing the environmental preferences of each species, can be selected locations that have favorable conditions for the reintroduction of species for several reasons, not colonized those sites and improve conservation actions in relation to actual settlements. The aim of this work was based on the definition of environmental conditions more favorable for the species of interest for conservation listed in the annexes of the Habitats Directive Armeria pseudarmeria, Dianthus cintranus subsp. cintranus, Verbascum litigiosum, Thymus villosus subsp. villosus, Ulex densus, Ruscus aculeatus, Omphalodes kuzinskyanae and Limonium multiflorum for future reintroduction of those species in places where there are not present, but these are favorable conditions for colonizing. And the definition of environmental conditions more favorable for the species, which although not listed in the annexes of the Habitats Directive, are associated with species that have conservation interest, including Armeria is welwitschii, Ulex jussiaei subsp. congestus, Daucus halophilus, Limonium virgatum and Ilex aquifolium. Yielding as final result the ecological profile of each species, thereby improving the knowledge concerning the target species for a better conservation strategy and a theoretical foundation that will serve as a tool for future reintroduction of these species in the classified sites Peniche/Santa Cruz and Sintra/Cascais in Natura 2000 network; EXTENDED ABSTRACT: The modelling of potential occurrence has been widely used for species of interest to conservation. Knowing the environmental preferences of each species, can be selected locations that have favorable conditions for the reintroduction of species for several reasons, not colonized those sites and improve conservation actions in relation to actual settlements. The aim of this work was based on the definition of environmental conditions more favorable for the species of interest for conservation listed in the annexes of the Habitats Directive Armeria pseudarmeria, Dianthus cintranus subsp. cintranus, Verbascum litigiosum, Thymus villosus subsp. villosus, Ulex densus, Ruscus aculeatus, Omphalodes kuzinskyanae and Limonium multiflorum for future reintroduction of those species in places where there are not present, but these are favorable conditions for colonizing. And the definition of environmental conditions more favorable for the species, which although not listed in the annexes of the Habitats Directive, are important tools because they are associated with species that have conservation interest, thereby improving the interpretation of results, including Armeria is welwitschii, Ulex jussiaei subsp. congestus, Daucus halophilus, Limonium virgatum and Ilex aquifolium. Yielding as final result the ecological profile of each species, thereby improving the knowledge concerning the target species for a better conservation strategy, a theoretical foundation that will serve as a tool for future reintroduction of these species and yet all the knowledge to mapping the potential occurrence of these species in the study area, in other words, the classified sites Peniche/Santa Cruz and Sintra/Cascais in Natura 2000 network. There are several methods for selecting preferences environmental conditions for each species, in this work was used the hierarchicalcluster analysis , along with a statistical analysis using GLMs (general linear models) to quantitative environmental variables (Slope, elevation, distance to the coast) and cross-tabulation for qualitative variables (geology and aspect). It was made clusters with the sampling points to see if there were sufficiently heterogeneous groups in relation to environmental conditions for better representation of the combination of environmental conditions, thus justifying the division of the groups. The same procedure was done for the species thereby verifying whether there is any connection between them in relation to their distribution, and to verifying some consistency with the selected inventory to avoid errors in the species survey. For these two procedures, we used a method of Hierarchical cluster analysis using Ward's method, and Euclidean Distance Squared as a measure of similarity. The hierarchical cluster analysis is the main statistical method to form relatively homogeneous groups of cases based on individual calculations of distances. After grouping the individual cases proceeded to justify the division of the different clusters,for this we used the general linear models (GLM), where each cluster was crossed with the environmental variables, thus justifying the division of the different clusters (since the clusters are interpreted through the variables included in them). Then each cluster of point samplings was crossed with each species (using GLM) and finally the environmental variables were crossed with each species (using GLM and Cross-tabulation). The environmental conditions where each species occurs, in other words, the ecological profile for each species was interpreted taking into account the cluster of point samplings wherein each is, the crossing of different environmental variables with each species and the crossing places of occurrence with the species. In this work were defined the preferred environmental conditions that each species listed in the annexes of the Habitats Directive by itself, giving more information on the favorable conditions where these species can be reintroduced or reinforced to the population level.The species that are not listed in the annexes of the Habitats Directive but are associated with habitats where species conservation interest occur, were extremely important and helped to define with greater certainty their preferred values, being considered good indicators of its occurrence. However, for the aspect values were not possible to obtain conclusive results for all species, shown to be a negligible factor to its distribution in this work.